Modeling of flexible deformable object for robotic manipulation - Hou Y.C.; Sahari K.S.M.; How D.N.T. (Institute of Electrical and Electronics Engineers Inc., 2023)
Gravitation; Intelligent control; Intelligent robots; Robotics; Smart sensors; Deformable modeling; Initial conditions; Integration method; Particle position; Path optimizations; Robotic applications; Robotic manipulation; Vision recognition; Deformation